Atlas of liver pathology - Kanel, Gary C.; Korula, Jacob (Atlases in diagnostic surgical pathology, 2005)
Offers readers with visual coverage of the microscopic and macroscopic appearance of the full range of hepatic disorders, both neoplastic and non-neoplastic. This title reflects the World Health Organization classification of liver and biliary tract diseases, and provides 60 per cent more images.